2017
DOI: 10.1371/journal.pone.0186634
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism as a risk factor for open angle glaucoma: A systematic review and meta-analysis

Abstract: PurposeThe relationship between hypothyroidism and primary open angle glaucoma (POAG) has attracted intense interest recently, but the reported results have been controversial. This meta-analysis was carried out to determine the association between hypothyroidism and POAG.MethodsThe literature was identified from three databases (Web of Science, Embase, and PubMed). The meta-analyses were performed using random-effects models, with results reported as adjusted odds ratios (ORs) with 95% confidence intervals (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
1
9
0
12
Order By: Relevance
“…Among the 52 included eligible MAs, 4628–73 (46/52, 88.5%) were published in English, and the rest74–79 (6/52, 11.5%) were published in Chinese. The 52 included MAs contained 685 studies, with an average of 13.2 (range: 3–39) studies per article.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 52 included eligible MAs, 4628–73 (46/52, 88.5%) were published in English, and the rest74–79 (6/52, 11.5%) were published in Chinese. The 52 included MAs contained 685 studies, with an average of 13.2 (range: 3–39) studies per article.…”
Section: Resultsmentioning
confidence: 99%
“…Ten39 40 43 49 57 58 65 68–70 MAs were about the associations between OH and other diseases, and 3528–36 38 42 44–47 50–56 59–64 66 67 75–79 MAs have shown the associations between SCH and other diseases. Seven37 41 48 71–74MAs have investigated the effects of both OH and SCH on other diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Zusätzlich sind Störungen in der Schilddrüsenfunktion beschrieben worden. Während für die endokrine Orbitopathie keine erhöhte Assoziation zum POWG nachgewiesen werden konnte [33 -35], zeigte sich in einer Metaanalyse die Hypothyreose als ein Risikofaktor für das POWG [36]. Als Ursachen käme eine hypothalamische Störung oder auch z.…”
Section: Stoffwechselstörungenunclassified
“…Research provides conflicting results regarding the link between hypothyroidism and glaucoma. Two recent reviews and meta-analyses (6,7) showed that the risk of glaucoma is significantly higher in patients with hypothyroidism -one of them analysed glaucoma in general (6) and another one POAG only (7). On the other hand, there is no increased risk of hypothyroidism in patients with glaucoma (6).…”
Section: Hypothyroidismmentioning
confidence: 99%
“…According to a hypothesis postulated by Smith et al (1992), hypothyroidism is associated with increased deposition of muco polysaccharides and hyaluronic acid in the trabecular meshwork, which leads to decreased aqueous outflow and results in intraocular pressure elevation (6,7). Additionally, both conditions might be linked with autoimmunity and there is a possibility of shared genetic autoimmune predisposition (6).…”
Section: Hypothyroidismmentioning
confidence: 99%